Concordância e reprodutividade da versão eletrônica dos questioários WHOQL-BREF e WHOQOL-OLD - Casamali, Flavia Fernanda Cunha (2017)
Introduction: Evidence of the validity of instruments for assessing health-related quality of life (QoL) are fundamental to grant interpretations and direct actions at the level of promotion and health care. Purpose: To verify the agreement and reproducibility of the QoL assessment instruments WHOQOL-Bref and WHOQOL-Old, in printed (PV) and online version (OV), called WHOQOL-Bref web and WHOQOL-Old web, respectively. Subjects and Method: A cross-sectional study was performed with 98 elderly people, separated into two groups, from Tapejara-RS, Brazil, during 2016 and 2017. The WHOQOL-bref and WHOQOL-old instruments applied in the PV and OV were answered individually. Results: Accordance between the online and the printed version was excellent for the general scores (ICC> 0.94) and for the specific domains (ICC> 0.80), except for the WHOQOL-bref domains (ICC> 0.67) and Autonomy (ICC> 0.78) of the WHOQOL-old. No differences were observed between the WHOQOL-bref and WHOQOL-old questionnaire scores, among the replicates (reproducibility and accordance). Conclusion: The web versions of the WHOQOL-bref and WHOQOL -old questionnaires presented good evidence of accordance and reproducibility.